Thyrotropin-Releasing Hormone Receptor (TRHR) Gene Is Associated With Essential Hypertension - García, Silvia I.; Porto, Patricia I.; Dieuzeide, Guillermo; Landa, María S.; Kirszner, Tobias; Plotquin, Yanquel; Gonzalez, Claudio; Pirola, Carlos J. (Hypertension (Dallas, Tex. 1979), 2001)
In essential hypertension, a polygenic and multifactorial syndrome, several genes interact with the environment to produce high blood pressure. Thyrotropin-releasing hormone (TRH) plays an important role in central cardiovascular regulation. We have described that TRH overexpression induces hypertension in a normal rat, which was reversed by TRH antisense treatment. This treatment also reduces the central TRH hyperactivity in spontaneously hypertensive rats and normalizes blood pressure. Human TRH receptor (TRHR) belongs to the G protein-coupled seven-transmembrane domain receptor superfamily. Mutations of these receptors may result in constitutive activation. As it has been demonstrated that hypertensive patients have a blunted TSH response to TRH injection, suggesting a defect in the TRHR, we postulate that the TRHR gene is involved in human hypertension. We studied 2 independent populations from different geographic regions of our countrya sample of adult subjects from a referral clinic and a population-based sample of high school students. In search of molecular variants of TRHR, we disclosed that a polymorphic TG dinucleotide repeat (STR) at −68 bp and a novel single nucleotide polymorphism, a G→C conversion at −221 located in the promoter of the TRHR are associated with essential hypertension. As STRs detected in gene promoters are potential Z-DNA-forming sequences and seem to affect gene expression, we studied the potentially different transcriptional activity of these TRHR promoter variants and found that the S/−221C allele has a higher affinity than does the L/G−221 allele to nuclear protein factor(s). Our findings support the hypothesis that the TRHR gene participates in the etiopathogenesis of essential hypertension.